The way of the ship : - Roland, Alex (John Wiley & Sons, 2008)
The history of shipping in America, as traditionally recounted, is based primarily on the fortunes of the American merchant marine. This book offers a global perspective and considers oceanic shipping and domestic shipping along America's coasts and inland waterways, with explanations of the forces that influenced the way of the ship. The result is an eye-opening look at American maritime history and the ways it helped shaped the nation’s history